Variability of environmental factors of an eastern Mediterranean Sea river influenced coastal system - KORMAS, K.AR.; NICOLAIDOU, A.; THESSALOU-LEGAKI, M. (Mediterranean Marine Science, 2003)
Spercheios River discharge rates of nutrients, suspended particulate matter (SPM) and particulate organic carbon (POC) and seawater concentrations of these parameters as well as chlorophyll a(chl a) were measured in the Maliakos Gulf, Greece, on a monthly basis between 1992-1993. From all the nutrients measured, silicate showed the highest discharge rates followed by nitrate, phosphate and nitrite. The river introduced significant amounts of SPM (8.5 – 35.5 Kg d -1 ) with very low POC content (<3%). Most of the variables measured showed no gradient from the river to the outer gulf, which could be attributed to fast mixing of the incoming water. However, chl a had higher concentrations in the inner (0.3 – 4.9 Μg l -1 ) and lower in the outer gulf (0.05 – 2.5 Μg l -1 ). It is suggested that the nutrients introduced by the river are consumed faster in the inner gulf and that a number of temporal streams and non-point sources at the periphery of the gulf prevent the formation of a gradient.